Novel benzopsoralen analogues : synthesis, biological activity and molecular docking studies - Francisco, Carla Santana (2014)
New benzopsoralen analogues were synthesized and their inhibitory effect on the growth of tumourtumour cell lines (MDA MB231 and TCC-SUP) was evaluated. The in vitro antitumour activity of the new benzopsoralen analogues was discussed in terms of structure–activity relationship. Molecular docking studies with human-CYP2A6 enzymes were also carried out with the synthesized compounds to evaluate the potential of these molecules to interact with the haem group of the enzymes. The results demonstrated that the compounds that are able to interact with the iron ion of the haem cofactor and at the same time with active site Asn297 are those that have better anti-proliferative activity.